Bacterial Natural Compounds with Anti-Inflammatory and Immunomodulatory Properties (Mini Review) - Jenab A; Roghanian R; Emtiazi G (Dove Medical Press, 2020)
Anahita Jenab, Rasoul Roghanian, Giti Emtiazi Biological Science and Technology, Department of Cellular and Microbiology, University of Isfahan, Hezar Jerib, Isfahan, IranCorrespondence: Anahita Jenab Tel/ Fax +983137932455Email anahitajenab@gmail.comAbstract: Inflammation is part of the body’s complex biological response to harmful stimuli such as damaged cells, pathogens, or irritants. It is a protective response involving blood cells, immune cells, and molecular mediators. The inflammation not only can eliminate the primary cause of cell injury but also clears out necrotic cells, tissue damaged from the original insults and inflammatory process. Furthermore, it can initiate tissue repair. Pro-inflammatory cytokines are produced predominantly by activated macrophages and are involved in the up-regulation of inflammatory reactions. They are involved in further regulating inflammatory reactions. There is ample evidence that some pro-inflammatory cytokines, such as interleukin 1β (IL-1β), IL-6, and tumor necrosis factor-α (TNF-α), are involved in the pathological pain process. Some of the natural compounds promote cytokines production and inhibit inflammatory responses. The natural compounds which are produced from microorganisms such as omega-3 fatty acid, cyclic peptide, antimicrobial peptide, oligosaccharides, and polysaccharides can reduce inflammation and could be easily incorporated into the diet without any adverse effects. For example, SCFA (short-chain fatty acids), peptide bacteriocin, and polycyclic peptide bacteriocin (nisin) could be used in the treatment of atherosclerosis, orthopedic postoperative infections, and mycobacterium tuberculosis infection, respectively. Also, fatty acids (saturated and unsaturated fatty acids) can be introduced as anti-inflammatory drugs. This review article summarizes bacterial natural compounds with modulating effects on cytokines that are surveyed which may have potential anti-inflammatory drug-like activity.Keywords: bacterial natural materials, secondary metabolite, drug-like activity, anti-inflammatory activity, cytokine